Nest-Plant Correlation and Predator Preclusion in Asian Openbill Storks (Anastomus ascitans):A Case Study from Nawabgunj Bird Sanctuary, India - Garg, Arti (Indian Forester, 2016)
The Asian openbill storks (Anastomus oscitans) build their nests underproper concealment for predation preclusion to protect eggs and nestlings and their wall construction is a meticulous task. The tree species Acacia nilotica and Prosopis juliflora, on islands is the most preferred nest-site and nest building matrial are extracted from Acacia nilotica, Barringtonia acutangula, Cynodon dactylon, Cypnerus rotundus, Eucalyptus citriodora, Prosopis juliflora and Terminalia arjuna. Conservation of these plant species is therefore, integral for nesting process of Asian open bill storks which constitute the most dominant migratory bird species .